Pemanfaatan Sosial Media Kegiatan Promosi dan Sistem Pembayaran Qris Mempermudah Transaksi Pembayaran pada A.A Transport - Desak Ayu Sriary Bhegawati; Dewa Ayu Kadek Pramita; I Putu Angga Baskara (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity focuses on improving the competitiveness of A.A Transport, a business that lacks cashless payment options and an effective social media marketing strategy. Providing cashless payments is a modern, customer-centric approach that differentiates businesses in a competitive market. Unfortunately, A.A Transport currently lacks such an option, providing an opportunity for improvement. This community service activity aims to assist A.A Transport in adopting cashless payment methods and the importance of effective social media marketing for MSMEs. Social media serves as a direct channel for interaction, building relationships, and expanding the market. The methods used in this community service activity were observation, interviews, surveys, and mentoring. The results achieved are in line with the project objectives, as A.A Transport successfully integrated QRIS for cashless payments and utilized social media effectively for marketing, thus contributing to its competitiveness and overall market reach.